Advanced FEM for free surface flow with application to landslides. Issue 1 (October 2016) - Schauer, Marco; Reinstädler, Sven; Dinkler, Dieter
Abstract: An advanced space‐time finite element method is presented to investigate movements of landslides and their interaction with flexible structures. The mechanics of liquefied soil is described by Navier‐Stokes‐equations for visco‐plastic non‐newtonian fluid. Likewise the fluid the kinematics of the structure is described by velocities, taking large rotations into account. This leads to a monolithic fluid‐structure interaction approach considering the multi‐field problem as a whole. The discretized model equations are assembled in a single set of algebraic equations, which are solved by applying Newton‐Raphson scheme. Free surface motion of landslide is described by the level‐set method. To reduce computational effort the fragmented finite element method is used, where only active finite elements are evaluated. A pde‐based extrapolation of the velocity‐field is applied to ensure an accurate transport of distance function, which defines the profile in space and time of the free surfaces. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)